Compliance e legislação eleitoral: uma ferramenta de resgate da confiança dos partidos políticos no Brasil - Lima, Roberto Wagner Lourenço (Universidade do Vale do Rio dos Sinos, 2022)
This master's thesis deals with a fundamental theme for Democracy: trust in political parties. Democracy has been experiencing a perennial crisis since its birth, substantially due to the permanent wound of corruption. The relationship between corruption and political parties for the seizure of power is one of the most complex facets to be dealt with and minimized in power games. Since the advent of Law 12,846/2013, Brazil has been fighting a more intense battle in the fight against corruption in the relations between private legal entities and the public power, and progress is slow. The law specifies some subjects, but silences others. In this work we will defend its immediate application to political parties while a specific legislation is not elaborated. So, integrity or compliance programs are a tool that can prove to be effective. The hypothesis that will be worked on is that the implementation and execution of effective integrity programs must become a powerful instrument of social control and this will allow the parties to act with a greater range of fairness and credibility. We have the general objective of the dissertation to analyze the implementation and applicability of business compliance programs in the conduct of political-party life aiming at carrying out both electoral campaigns and party life with less disproportionate influence of economic power and more isonomic. To this end, the work proposes, through specific objectives, to: Identify Compliance as an element of corporate culture and its applicability in the electoral field; demonstrate that the application of integrity programs in political parties, as well as in companies and their corporate relationships, brings gains to political life; Check the necessary and useful incentives for the implementation of the integrity program by political parties; and present a proposal for a booklet to implement an integrity program for Brazilian parties. Our methodology is based on the literature review on the subject and the verification of the actions that have been taken by the agents of this discussion, the parties, in the implementation of these tools. By way of conclusions, it was observed that the theme is practically ignored by the parties, even with their own manifestations in news published on their websites and in the press. From the outset, it is observed that only tough and specific legislation will force this implementation in the medium and long term.
Keywords: Democracia; Partidos políticos; Compliance; Integridade; Confiança; Democracy; Trust; ACCNPQ::Ciências Sociais Aplicadas::Direito